2016
DOI: 10.1016/j.ijplas.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying deformation processes near grain boundaries in α titanium using nanoindentation and crystal plasticity modeling

Abstract: We validate a model for the population dynamics, as they occur in a chemostat environment, of the green algae Raphidocelis subcapitata, a species that is often used as a primary food source in toxicity experiments for the fresh water crustacean Daphnia magna. We collected longitudinal data from 4 replicate population experiments with R. subcapitata. This data was fit to a logistic growth model to reveal patterns of the algae growth in a continuous culture. Overall, our results suggest that a proportional error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…While there is much discussion of slip transfer in the literature, there is relatively little experimental quantification of thresholds for observed slip transfer. From the experimental perspective, thresholds for slip transfer have been identified in nano-indentation experiments (Su et al, 2016;Xiao et al, 2017), and thresholds for specific boundaries have been identified in cantilever beam bending tests [Ding et al, 2016]. Analysis of slip stimulated mechanical twinning in Ti using surface electron back-scatter diffraction (EBDS) orientation measurements showed that slip transfer that nucleated mechanical twins was probable when " = cos cos > 0.9 (Wang et al, 2010), where ψ and κ are the angles between the slip plane normal and the Burgers vector directions, respectively, for each combination of slip systems 1 .…”
Section: Introductionmentioning
confidence: 99%
“…While there is much discussion of slip transfer in the literature, there is relatively little experimental quantification of thresholds for observed slip transfer. From the experimental perspective, thresholds for slip transfer have been identified in nano-indentation experiments (Su et al, 2016;Xiao et al, 2017), and thresholds for specific boundaries have been identified in cantilever beam bending tests [Ding et al, 2016]. Analysis of slip stimulated mechanical twinning in Ti using surface electron back-scatter diffraction (EBDS) orientation measurements showed that slip transfer that nucleated mechanical twins was probable when " = cos cos > 0.9 (Wang et al, 2010), where ψ and κ are the angles between the slip plane normal and the Burgers vector directions, respectively, for each combination of slip systems 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The second is due to the real effect that indents close to grain boundaries respond differently to indents performed in the centre of grains. Plastic zones that impinge upon grain boundaries can cause dislocation pile-up and slip transmission, or the grain boundary might act as a dislocation source/sink itself, strongly affecting measured hardness [50][51][52][53][54][55][56]. In order to avoid the influence of grain boundary-associated variation, and capitalising on the wealth of data available, points can be isolated based on spatial location relative to the microstructure.…”
Section: Dataset 0-nanoindentation Comparisons and Tip Calibration Persistencementioning
confidence: 99%
“…Grain boundaries are assumed to be transparent for slip transfer in standard (phenomenological) CP models and, thus, the effect of the grain boundary on the slip transmission is not accounted for. Physically-based CP models can introduce the effect of grain boundaries through different parameters that take into account the increase in dislocation density near the grain boundary (Mayeur et al, 2015;Su et al, 2016;Hauoala et al, 2018). Finally, lowerorder SGCP account for the effect grain boundaries through the density of GNDs generated near the boundaries due to the deformation incompatibility between grains with different orientations, while higher-order SGCP can control the dislocation flux across the boundary by means of the higher-order boundary conditions.…”
Section: Concluding Remarks and Future Developmentsmentioning
confidence: 99%